Visual and Non -- Visual Elements Found in "Bali Safari Park" Brochure - Tai, Emeliana; Tai, Emeliana; Santika Azola Sekarini, Komang; Nyoman Kardana, I; Sujaya, Nyoman (KnE Social Sciences, 2022)
This research was mainly aimed at finding out the visual and non-visual element and their meanings in Bali Safari Park brochure. The brochure was chosen because there were various types of pictures and texts. The data were collected by finding and reading that brochure and note taking the data from Bali Safari Park brochure using the observation method. The method that was used in analyzing the data was a descriptive method. The presenting the data was formal method by using symbols, pictures or images to illustrate the phenomena found in the data. The result of this research showed that there were the visual and non-visual elements found in Bali Safari Park brochure. The visual and non-visual elements were in the form of pictures, the logo, symbol, colors, the pictures of fonts, phrases, and sentences. Those forms were found in headline, body copy, signature line, and standing details. The types of meaning found in the visual and non-visual elements were affective meaning, conceptual meaning, and denotative meaning. Keywords: discourse analysis, visual and non-visual elements, Bali Safari Park